University social responsibility in Latin-American. The cases of URSULA and AUSJAL - Gaete Quezada, Ricardo (2019)
The social relevance of higher education institutions has increased considerably in the context of developing more sustainable, democratic and inclusive societies, in which the generation and transmission of knowledge has a growing value. Thus, the aim of the article is to analyze the presence of the concept of university social responsibility in the strategic planning of the institutions belonging to the Union of Latin American University Social Responsibility (URSULA in Spanish) and the Association of Confident Universities to the Society of Jesus in Latin America (AUSJAL in Spanish), as examples of Latin American interuniversity networks that aim to strengthen the role of universities in the Region. Through an analysis of quantitative content, information is gathered about the presence of social responsibility or socially responsible terms in mission statements and institutional vision, using descriptive statistics procedures for the analysis of data by drawing figures and frequency tables. The results show a low frequency of the aspects related to socially responsible behavior in the mission and vision statements analyzed, concluding that it is advisable to improve the coherence of the corporate philosophy declared in the strategic plans of the Latin American university institutions attached to both initiatives studied, allowing to consolidate more effectively the concept of university social responsibility both in the organizational culture and in the operational functioning of the institutions that belong to both initiatives..